Pretomanid for tuberculosis treatment: an update for clinical purposes - Sara Occhineri; Tommaso Matucci; Laura Rindi; Giusy Tiseo; Marco Falcone; Niccolò Riccardi; Giorgio Besozzi (Elsevier, 2022)
Coronavirus disease (COVID-19) pandemic determined a 10 years-set back in tuberculosis (TB) control programs. Recent advances in available therapies may help recover the time lost. While Linezolid (LZD) and Bedaquiline (BDQ), previously Group D second line drugs (SLDs) for TB, have been relocated to Group A, other drugs are currently being studied in regimens for drug resistant TB (DR-TB). Among these, Pretomanid (PA), a recently introduced antimycobacterial drug derived from nitroimidazole with both solid bactericidal and bacteriostatic effect, and with an excellent effectiveness and tolerability profile, is in the spotlight. Following promising data obtained from recently published and ongoing randomized controlled trials (RCTs), the World Health Organization (WHO) determined to include PA in its guidelines for the treatment of rifampicin-resistant (RR), multi drug resistant (MDR) and pre-extensively drug resistant TB (pre-XDR-TB) with BDQ, LZD and Moxifloxacine (MFX) in a 6-month regimen. Although further studies on the subject are needed, PA may also represent a treatment option for drug-susceptible TB (DS-TB), latent TB infection (LTBI) and non tuberculous mycobacteria (NTM). This narrative review aims to examine current implementation options and future possibilities for PA in the never-ending fight against TB.